2018
DOI: 10.3389/fimmu.2018.00770
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidyl-Inositol-3 Kinase Inhibitors Regulate Peptidoglycan-Induced Myeloid Leukocyte Recruitment, Inflammation, and Neurotoxicity in Mouse Brain

Abstract: Acute brain injury leads to the recruitment and activation of immune cells including resident microglia and infiltrating peripheral myeloid cells (MC), which contribute to the inflammatory response involved in neuronal damage. We previously reported that TLR2 stimulation by peptidoglycan (PGN) from Staphylococcus aureus, in vitro and in vivo, induced microglial cell activation followed by autophagy induction. In this report, we evaluated if phosphatidyl-inositol-3 kinase (PI3K) pharmacological inhibitors LY294… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…To confirm the regulatory effects of ERK and Akt phosphorylation on the expression of BDNF, synapsin-1, and SYT-1, we injected either ERK (U0126, 20 μM) or PI3K/Akt inhibitor (LY294002, 0.19 nmol) into the hippocampus (0.5 µL of 50 μM solution/site) stereotaxically in normal mice. It has been reported that these doses of U0126 and LY294002 were effective in blocking the signaling pathways in the brain tissues ( Arroyo et al, 2018 ; Wang et al, 2018 ). Twenty-four hours after the injection we found a significant decrease in the mRNA expression of Bdnf , synapsin-1, and SYT-1 in the hippocampus ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the regulatory effects of ERK and Akt phosphorylation on the expression of BDNF, synapsin-1, and SYT-1, we injected either ERK (U0126, 20 μM) or PI3K/Akt inhibitor (LY294002, 0.19 nmol) into the hippocampus (0.5 µL of 50 μM solution/site) stereotaxically in normal mice. It has been reported that these doses of U0126 and LY294002 were effective in blocking the signaling pathways in the brain tissues ( Arroyo et al, 2018 ; Wang et al, 2018 ). Twenty-four hours after the injection we found a significant decrease in the mRNA expression of Bdnf , synapsin-1, and SYT-1 in the hippocampus ( Supplementary Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…PGN receptors were reported to be highly expressed in neurons, and a transgenic mouse model of PGN-sensing molecules showed altered expression levels of synaptic-related genes and behavioral disorders, suggesting a possible association between PGN and the central neuron system [ 45 , 46 ]. Direct PGN injection into the mouse brain parenchyma induced microglial cell activation and neurotoxicity via the PI3K-dependent signaling pathway [ 47 ]. We investigated whether the in vivo injection of PGN could impair HSPC function by compromising bone marrow autonomic neuropathy, as we did not observe a direct effect of PGN on HSPCs ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have demonstrated novel roles for TLR2 and TLR4 in regulating microglial autophagy. Arroyo et al [101,102] reported that TLR2 stimulation enhances microglial autophagy via PI3K. TLR4 activation by lipopolysaccharide (LPS) reduces autophagic flux and Atg gene expression in microglia by inhibiting the PI3K-FOXO3 pathway.…”
Section: Toll-like Receptors (Tlrs)mentioning
confidence: 99%